Respuesta :

Answer:

[tex] x = 3\frac{1}{3}, \: \: x = - 3\frac{1}{3} [/tex]

Step-by-step explanation:

[tex]\frac{4 }{9} - \frac{x {}^{2} }{25} = 0 \\ \\ = { \bigg( \frac{2}{3} \bigg) }^{2} - { \bigg( \frac{x}{5} \bigg) }^{2} = 0\\ \\ { \bigg( \frac{2}{3} -\frac{x}{5} \bigg) }{ \bigg( \frac{2}{3} + \frac{x}{5} \bigg) } = 0 \\ \\ { \bigg( \frac{2}{3} -\frac{x}{5} \bigg) } = 0, \: \: { \bigg( \frac{2}{3} + \frac{x}{5} \bigg) } = 0 \\ \\ \frac{x}{5} = \frac{2}{3}, \: \: \frac{x}{5} = - \frac{2}{3} \\ \\ x = \frac{10}{3}, \: \: x = - \frac{10}{3} \\ \\ x = 3\frac{1}{3}, \: \: x = - 3\frac{1}{3} \\ \\ [/tex]